Can we design language education policy and curricula for a motivated learner? Self-Determination Theory and the UK language crisis. Issue 2 (4th March 2022) - Lanvers, Ursula; Graham, Suzanne
ABSTRACT : With the UK entering its fourth decade of this crisis with no end in sight, it is timely to ask how current policy directions for language learning beyond the compulsory phase (currently age 14 in all 4 UK nations) align with learners' psychological needs in relation to language learning. After a review of these psychological needs within motivational theory, this article first discusses current foreign languages (FL) policies in all four UK nations (England, Wales, Northern Ireland, Scotland), alongside the current debates around the recently published 2021 Ofsted Curriculum Research Review for languages (OCRR), which is likely to underpin Ofsted's inspections of provision in England. We then critically evaluate a range of research-based measures to boost learner motivation, some of which show promising results. Taking as our theoretical basis the psychological needs of autonomy, relatedness and competence that comprise Self-Determination Theory (SDT), we then analyse FL policy and practices directions in the UK, including those articulated in the OCRR, and conclude that these tend to ignore or misinterpret motivational theory. This is followed by recommendations for FL policy which align both with SDT principles and research evidence. The conclusion critically evaluates opportunities and risks of current UK policy directions.